The Effect of Storytelling Technique in Improving Students Speaking Ability at SMAN 1 Sidamanik - Sitanggang, Nikita; Siahaan, Basar Lolo; Turnip, Roni Ripaldi; Gultom, Destri (International Journal of Contemporary Studies in Education, 2023)
This research seeks to determine how the narrative method affects the speaking ability of SMAN 1 SIDAMANIK second-graders. This pre-experimental investigation with a population of thirty students selected groups using random cluster sampling. Before and after therapy, a narrative technique was used to collect data. Before and after the test, students receive instruction. The average score on the pre-test was 48.68, while the average score on the post-test was 54.97. Between the pre-test and post-test, the data indicate an increase. The research shows that the t-test is preferable to the t-table (4,827 > 2,04). The significant difference between the post-test and the pre-test suggests that the narrative method affects students' speaking ability. This demonstrates how a narrative approach can help students develop their public speaking abilities. The speaking component received the highest overall score, followed by syntax and speech, which received the lowest score, according to this research. Therefore, instructional methods must emphasize these elements.